2002
DOI: 10.1034/j.1600-0560.2002.290109.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell collagenoma: case report and review of the literature

Abstract: GCC is an unusual cutaneous fibrous tumor that should be differentiated from circumscribed storiform collagenoma, pleomorphic fibroma, regressive forms of dermatofibroma, and solitary myofibroma based on its histological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Therefore, it has been suggested that pleomorphic fibromas and sclerotic fibromas may be related lesions along a morphologic spectrum. Similarly, giant cell collagenomas 10 are probably a variant of sclerotic fibromas, given their histologic similarities. For now, it is reasonable to retain the different designations, given the somewhat different histologic features and the fact that, to our knowledge, pleomorphic fibromas and giant cell collagenomas have not been associated with Cowden's syndrome unlike the prototypical sclerotic fibroma.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that pleomorphic fibromas and sclerotic fibromas may be related lesions along a morphologic spectrum. Similarly, giant cell collagenomas 10 are probably a variant of sclerotic fibromas, given their histologic similarities. For now, it is reasonable to retain the different designations, given the somewhat different histologic features and the fact that, to our knowledge, pleomorphic fibromas and giant cell collagenomas have not been associated with Cowden's syndrome unlike the prototypical sclerotic fibroma.…”
Section: Discussionmentioning
confidence: 99%
“…This case suggests that the spectrum of CS-associated cutaneous lesions needs to be expanded to include GCC/PSF. As in previous case reports, even the solitary variant of SF has been a valuable cutaneous clue for the identification of previously undiagnosed CS, 7,10 adding GCC/PSF to the spectrum of CS-associated cutaneous T A B L E 1 (Continued) Reference Garcia et al 12 Martín-L opez et al 13 Chen et al 14 Brito et al 15 Rudolph et al 16 Ramos et al 17…”
Section: Ramos Et Al 17mentioning
confidence: 83%
“…16 Brito et al also described a similar appearing lesion diagnosed as GCC; however, the authors considered GCC to be a distinct entity from SF. 15 In 2002, with the use of electron microscopy, Ramos et al noted that SF can have giant multinucleate-looking cells that are actually groups of mononuclear cells opposed to each other. In comparison, true giant cells in GCC were noted to be ultrastructurally and immunophenotypically different from that of SF, exhibiting multinucleate cells with multiple individual nuclei, increased cytoplasmic rough endoplasmic reticulum, and a negative factor XIIIa staining, suggesting a different pattern of differentiation for the two similar appearing cutaneous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…( 1 - 4 ) Storiform collagenoma has as differential diagnosis other well-circumscribed skin tumors such as dermatofibroma, pleomorphic fibroma, sclerotic lipoma, fibrolipoma, giant cell collagenoma, benign fibrous histiocytoma, intradermal Spitz nevus and giant cell angiohistiocytoma. ( 5 - 8 )…”
Section: Introductionmentioning
confidence: 99%
“…( 1 - 4 ) Tem como diagnósticos diferenciais outros tumores cutâneos bem delimitados, como dermatofibroma, fibroma pleomórfico, lipoma esclerótico, fibrolipoma, colagenoma de células gigantes, histiocitoma fibroso benigno, nevo de Spitz intradérmico e angioistiocitoma de células gigantes. ( 5 - 8 )…”
Section: Introductionunclassified